Humoral immunity to SARS-CoV-2 in kidney transplant recipients and dialysis patients: IgA and IgG patterns unraveled after SARS-CoV-2 infection and vaccination - Caroline De Bouver; Jason Bouziotis; Veerle P. W. M. Wijtvliet; Kevin K. Ariën; Joachim Mariën; Leo Heyndrickx; Marie M. Couttenye; Hans J. W. de Fijter; Fabienne Mestrez; Serge Treille; Olivier Mat; Frederic Collart; et al. (Virology Journal, 2024)
Abstract Background Infection with SARS-CoV-2 in high-risk groups such as kidney transplant and dialysis patients is shown to be associated with a more serious course of the disease. Four years after the start of the COVID-19 pandemic, crucial knowledge on the immune responses in these patient groups is still lacking. Therefore, this study aimed at investigating the humoral immune response after a SARS-CoV-2 infection compared to vaccination as well as the evolution of immunoglobulins over time. Methods Kidney transplant recipients, patients on haemodialysis or on peritoneal dialysis and healthy controls were included in this longitudinal multicenter study. SARS-CoV-2 anti-RBD, anti-NP and anti-S1S2 immunoglobulin G (IgG) and A (IgA) as well as the neutralizing antibody capacity were measured. Results Kidney transplant recipients had a significantly better humoral response to SARS-CoV-2 after infection (86.4%) than after a two-dose mRNA vaccination (55.8%) while seroconversion was comparable in patients on haemodialysis after infection (95.8%) versus vaccination (89.4%). In individuals without prior COVID-19, the IgG levels after vaccination were significantly lower in kidney transplant recipients when compared to all other groups. However, the IgA titres remained the highest in this patient group at each time point, both after infection and vaccination. A history COVID-19 was associated with higher antibody levels after double-dose vaccination in all patient categories and, while decreasing, titres remained high six months after double-dose vaccination. Conclusion Kidney transplant recipients had a more robust humoral response to SARS-CoV-2 following infection compared to a two-dose mRNA vaccination, while patients on haemodialysis exhibited comparable seroconversion rates. Notably, individuals with prior COVID-19 exhibited higher IgG levels in response to vaccination. Hybrid immunity is thus the best possible defence against severe COVID-19 disease and seems also to hold up for these populations. Next, it is not clear whether the higher IgA levels in the kidney transplant recipients is beneficial for neutralizing SARS-CoV-2 or if it is a sign of disease severity.